Study on the effect of decompression music on anxiety patients based on emotion classification algorithm (Informatica, 2024)
The relief of anxiety is important for physical health. This paper briefly introduces music therapy and the multimodal fusion-based emotion classification algorithm used to accurately select appropriate emotion music for music therapy. Afterwards, the algorithm was first tested in an experiment, and then the efficacy of music therapy was tested with 80 contemporaneous anxiety patients from XX Hospital in Binzhou City, Shandong Province. The results showed that the multimodal fusion-based music emotion classification algorithm was sufficiently accurate; conventional medication and care were also effective in relieving the anxiety symptoms, but music therapy further alleviated patients’ anxiety.